Evaluating village financial governance in top tourism destinations - Yap, Nonni; Nugroho, Mulyanto; Rachmiyati, Nekky (Edelweiss Applied Science and Technology, 2024)
Village fund management is important for village economy and welfare. Village funds in Gresik Regency, Indonesia In particular, for the 2022 period, the revenue budget is IDR. 2,355,638,000 in Pangkahkulon village, while Rp. 9,865,701,000 for Sekapuk village, demonstrating the principles of accountability and transparency for effective and sustainable development. Accountability and transparency in village fund management ensure clear financial reporting, community participation, and openness of information, despite still facing obstacles such as lack of resources and regulations. Lack of community participation reduces accountability, transparency in achieving good financial governance in 3 villages in Gresik Regency. This study proposes to assess the impact of financial governance in Sekapuk, Pangkahkulon, and Sidokumpul Villages, focusing on accountability, transparency, and community participation. Despite progress, challenges including resource constraints and regulatory changes remain. This study provides in-depth insights into the effectiveness of village financial management systems, emphasizing the importance of community participation in improving accountability and transparency and building public trust. This study explores the implementation of good financial governance in three Gresik villages, focusing on accountability, transparency, and community participation. The study design uses a phenomenological approach to understand perceptions related to transparency and accountability in village fund management in Gresik Tourism Villages through interviews and observations. Primary data were collected from village officials, and analysis was conducted using NVivo 12 Plus, prioritizing transparency and community participation. This study found that accountability in Gresik Tourism Villages requires a transparent and efficient financial system. The SISKEUDES application experienced technical problems that affected reporting, so technical improvements and staff training were needed. Transparency and community participation in meetings and discussion forums are key to increasing trust and effectiveness in village fund management. Thus, in achieving Good Financial Governance in Gresik Tourism Villages, a financial system that is accountable, transparent, and involves community participation is needed. Information technology, regular training, and supervision with NGOs are important for efficiency and transparency, and discussion forums strengthen community trust.